CURRENT BIOMARKERS FOR MYOCARDIAL INFARCTION - RATHISH. R; GAYATHRI GUNALAN; SUMATHI. P (International Journal of Pharma and Bio Sciences, 2013)
Myocardial infarction (MI) is a medical condition that occurs, when a coronary artery is severely blocked by vulnerable plaque and as a result, there is a significant reduction or break in the blood supply leading to cardiac damage. Cardiac biomarkers play a major role in the investigation of MI. The current study focused on the lipid profile patterns and cardiac biomarker levels in MI patients and in MI prone subjects. The study also discusses on the role and sensitivity of Troponin I over other biomarkers. The study was carried out in three groups viz., normal subjects, MI prone subjects and MI patients. Lipid profile and cardiac biomarkers like Troponin I, CK, CKMB, SGOT were analyzed in all three groups and compared. Increased levels of Total cholesterol, Triglyceride, Low density lipoprotein (LDL), Very low density lipoprotein (VLDL) were observed in both MI patients and MI prone category (P<0.001), whereas the level of High density lipoprotein (HDL) was decreased in both the study groups compared to the normal control. Elevated levels of Troponin I, Creatine Kinase(CK), CK-MB and Aspartate transaminase (AST/SGOT) were noticed in MI patients relative to other groups. MI prone subjects were found to have discordant biomarker levels in their blood with normal Troponin I, SGOT levels and elevated CK, CKMB levels. Troponin I is specific and sensitive to cardiac damage and hence can be used in the diagnosis of MI and early detection of cardiovascular risk. Subjects prone to CVD can be found out by their lipid profile patterns and discordant biomarker levels.